Dampak Pergeseran Tenaga Kerja Tambak Garam di Kabupaten Cirebon - Nurhannah Widianti (Empower : Jurnal Pengembangan Masyarakat Islam, 2020)
The purpose of this study, namely (1) to describes the causes of the local workforce of the affected areas unable to enter the industrial sector; (2) describe the role of government, and industry in anticipating the emergence of unemployment in industrial affected areas. The research method used is a qualitative method with a population of 519 people who originally worked on salt land. Meanwhile, the sample data sources were selected purposively with a sample of 100 people determined through Slovin formula. The data collection technique of this study uses triangulation: interviews, observation, and documentation studies. The results of the study showed: (1) former salt farmers as local laborers did not have adequate administrative, technical, and technological skills that were difficult to absorb in the industrial sector; (2) the government and industry need to build industrial estates that are friendly to local labor. Skills that are skilled and capable of mastering technology in the power generation industry must also be prepared. Its implementation, that is, can be through the establishment of vocational schools that are in accordance with industry needs.